Integrasi Program Reguler Sekolah Dan Program Non Reguler Dalam Meningkatkan Hasil Belajar PAI Di Tingkat Sekolah Dasar Kota Cirebon - cawin cawin (Eduvis : Jurnal Manajemen Pendidikan Islam, 2020)
Lately, the issues of radicalism have become an interesting topic in some circles, especially academics. The issue of radicalism has become a topic of discussion in the public domain lately due to the very structured radical movements in Indonesia which are marked by the emergence of new groups, sects, groups and groups in the name of Islam. Integrating pesantren model education into formal school education. That is, schools as a formal institution have first, then the Madrasah education system is adopted and applied to the Cirebon City Elementary School. Based on the background of the above problems the authors conducted research with the aim of: (a) To find out the integration of regular school programs and non-regular programs in PAI subjects at the elementary school level, (b) To know the effectiveness of the integration of regular school programs and non-regular programs on reading skills, writing and memorizing the Koran at the elementary school level (c) To know and analyze obstacles in carrying out the integration of regular school programs and non-regular programs, (d) to find out solutions in dealing with the obstacles of integration of regular school programs and programs non-regular in improving the ability to read, write and memorize the Qur'an. The method used is to use a qualitative approach. This is based on problems and objectives to be achieved that is only trying to describe or describe comprehensively about the data obtained in the field about the Integration of Regular and Non-Regular School Programs in improving the learning outcomes of PAI, regarding behavior, events, or certain places in detail and deep. Data collection is done by observation, documentation, and interview techniques. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The conclusion of this study is the process of memorizing the Qur'an at the elementary school level needs to be pursued how to be able to influence and cause intrinsic motivation (motivation in oneself), through structuring the right method, which is able to encourage the growth of student motivation in learning. Abstrak Mengintegrasikan pendidikan model pesantren kedalam pendidikan formal sekolah. Artinya, sekolah sebagai lembaga formal telah terlebih dahulu, baru kemudian sistem pendidikan Madrasah diadopsi dan diterapkan pada Sekolah Dasar Kota Cirebon. Berdasarkan latarbelakang masalah diatas penulis melakukan penelitian dengan tujuan : (a) Untuk Mengetahui integrasi program reguler sekolah dan program non reguler pada mata pelajaran PAI di tingkat Sekolah Dasar, (b) Untuk Mengetahui Efektifitas integrasi program reguler sekolah dan program non reguler terhadap kemampuan membaca, menulis dan Hafalan Al-Qur’an di tingkat Sekolah Dasar (c) Untuk Mengetahui dan Menganalisis hambatan-hambatan dalam menyelenggarakan integrasi program reguler sekolah dan program Non reguler, (d) Untuk Mengetahui Solusi dalam menghadapi hambatan-hambatan integrasi program reguler sekolah dan program non reguler dalam meningkatkan kemampuan membaca, menulis dan hafalan al-qur’an. Metode yang digunakan adalah menggunakan pendekatan kualitatif. Hal ini didasarkan pada permasalahan dan tujuan yang hendak dicapai yaitu hanya berusaha untuk menggambarkan atau mendiskripsikan secara komprehensif mengenai data yang diperoleh di lapangan tentang Integrasi Program Reguler sekolah dan Non Reguler dalam meningkatkan hasil belajar Pai, mengenai prilaku, peristiwa, atau tempat tertentu secara rinci dan mendalam. Pengumpulan data dilakukan dengan teknik observasi, dokumentasi, dan wawancara. Teknik analisis data meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Kesimpulan dari penelitian ini adalah proses hafalan Al-Qur’an pada tingkat sekolah Dasar perlu diupayakan bagaimana agar dapat mempengaruhi dan menimbulkan motivasi intrinsik (motivasi dalam diri), melalui penataan metode yang tepat, yang mampu mendorong tumbuhnya motivasi belajar dalam diri siswa